Human Immunodeficiency Virus/AIDS in the Era of Coronavirus Disease 2019: A Juxtaposition of 2 Pandemics. (7th April 2021) - Eisinger, Robert W; Lerner, Andrea M; Fauci, Anthony S
Abstract: The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted persons with human immunodeficiency virus (HIV), interfering with critical health services for HIV prevention, treatment, and care. While there are multiple profiles of persons living with HIV and the impact of COVID-19 may differ for each, the severity of COVID-19 in persons with HIV is related strongly to the presence of comorbidities that increase the risk of severe disease in COVID-19 patients in the absence of HIV. An effective response to the juxtaposition of the HIV and COVID-19 pandemics requires a novel coordinated and collaborative global effort of scientists, industry, and community partners to accelerate basic and clinical research, as well as implementation science to operationalize evidence-based interventions expeditiously in real-world settings. Accelerated development and clinical evaluation of prevention and treatment countermeasures are urgently needed to mitigate the juxtaposition of the HIV and COVID-19 pandemics. Abstract : Concurrent COVID-19 and HIV/AIDS pandemics pose unprecedented societal, economic, and public health challenges worldwide. Effective responses to these dual pandemics require a novel coordinated and collaborative global effort to accelerate biomedical research and implementation science to operationalize evidence-based interventions expeditiously.